Recursos institucionais e o desenvolvimento da pós-graduação stricto sensu nas universidades federais - Andrade, Elida Furtado da Silva (2019)
The growth of stricto sensu graduate programs requires administrative and academic organization work. The top management from institutions must practice this skill. Thus, the importance of the performance of senior management of federal universities in the elaboration and definition of the strategies to be adopted in order to achieve the consolidation of their post-graduate programs, using strategic evaluation. Thus, this work aims to analyze how the postgraduate pro-rectors of the federal universities allocate the institutional resources to develop the stricto sensu postgraduate course. A case study conducted the procedure chosen for this research and, for data collection, the documentary research and interviews with graduate pro-rectors of three federal universities based in the north and center-west regions. To determine the research units involved in this study, the guidelines emanated in the National Postgraduate Plans that deal with the fight against regional asymmetries, especially those that refer to the geographical distribution in the offer of stricto sensu graduate courses, were observed. Thus, the federal universities of Mato Grosso / UFMT, Amazonas / UFAM, based in the legal Amazon region, and Mato Grosso do Sul / UFMS, based in the central-west region, were defined as the object of study, in the period from 2008 to 2017, a similar performance in the periodic evaluations carried out by CAPES and that share similar needs and fragilities to develop the stricto sensu postgraduate in the institutional scope. The contributions of this work are essentially in the practical and managerial field, expressed through the proposal of the model of allocation of institutional resources for the development of the stricto sensu postgraduate course. However, theory improvement was by identifying a new possibility of arrangement for analysis of internal resources of the organization, expanding the view of the VRIO model, by proposing the existence of a resource with all the attributes indicated in this model to identify a strategic resource, with the exception of one, that refers to the Organization.